Kinetics and Mechanism of Oxidation of m-/p-Nitrobenzaldehydes by Quinolinium Bromochromate in Acetic Acid-Perchloric Acid-Water Medium - HIRAN, B.L.; MALKANI, R.K.; CHOUDHARY, PAKARAM; JAIN, SAPANA (Asian Journal of Chemistry, 2010)
Oxidation of benzaldehyde, p-nitro- and m-nitrobenzaldehydes by quinolinium bromochromate (QBC) inaquo-acetic acid medium is first order each in QBC and benzaldehyde while second order with respect to H+. The products of oxidation are the corresponding benzoic acids and Cr(llI). The oxidation of deuterated benzaldehyde exhibits a substantial primary kinetic isotope effect. Formation of chromic-ester between hydratedbenzaldehydes and protonated quinolinium bromochromate, followed by C-H bond fission in slow step, explains the observed experimental facts. The order of reactivity in benzaldehydes is p-NO2> m-NO2 > H. Activation parameters for the observed rate constant have been evaluated.